Hyponatremia in ultradistance triathletes - Thompson, J. M; Campbell, R. G.; Kuttner, J. A.; Boswell, D. R. (Medicine & Science in Sports & Exercise, 1999)
Hyponatremia is a common biochemical finding in ultradistance triathletes but is usually asymptomatic. Although mild hyponatremia was associated with variable body weight changes, fluid overload was the cause of most (73%) cases of severe, symptomatic hyponatremia.